MECHANISM OF TAX-PAYER’S LIABILITY IN REALIZATION OF THE BUSINESS GOAL DOCTRINE - S. P. Bortnikov (Russian Journal of Economics and Law)
Objective: to prove that the mechanism of business goal doctrine realization forms a new type of liability in tax relations. Methods: The methodological basis of the research is dialectics method allowing to reveal the properties of liability institution in its development; comparative and synthetical methods allowed to analyze the business goal doctrine realization in protective relations. Results: Basing on the carried out analysis we can state that the court practice realizing the business goal doctrine has elaborated the new form of liability in tax relations, not stipulated by the Russian Taxation Code. Scientific novelty: Elaborated and for the first time introduced into science the conceptual theoretical-legal provisions concerning the actual business goal and the appropriateness of using the taxation incentives as a tax-payer’s liability. The mechanism of tax liability determination by private law facts is revealed, when a tax-payer either abuses one’s rights or views a tax incentive as entrepreneur’s income, not relating to its purpose. Practical value: The theoretical provisions formulated in the research can be used in scientific, law-making and law enforcement activity, in educational process of higher professional educational institutions of juridical profile, in qualification improvement of scientific-educational personnel in the sphere of jurisprudence.